Group of women at Bible class - Gordon, John C. (photographer):::Creator::::::::::::
This photograph shows a group of women gathered together in a room for Bible class. They all have Bibles in their hands and most of them appear to be listening to one woman speaking. The woman speaking may be Mrs. Washburn who was the class teacher.